1989
DOI: 10.1021/ar00162a002
|View full text |Cite
|
Sign up to set email alerts
|

Dioxiranes: a new class of powerful oxidants

Abstract: Ace. Chem. Res. 1989,22, 205-211 205 unenriched while the cis-trans isomer and 10 must be enriched. This was confirmed for 612. Photolysis at 10 "C of cis-612 gives p = 0, 90, 128% (130%) for cis-612, trans-(i12, and lol2, respectively, whereas photolysis of t r~n s -6 ,~ gives ( 3 = 68, 2, 131% for the same three compound^.^^ This confirmation strongly supports the above model.In summary, the physical basis for the difference in 13C enrichment among the products of biradical decay is the inherent tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 631 publications
(231 citation statements)
references
References 74 publications
6
221
0
4
Order By: Relevance
“…52-56, 62, 68, 69, 89, 90, and 101-107). The primary frontier orbital interaction for both spiro and planar approaches is between the highest occupied molecular orbital of the alkene ( of CAC) and the lowest unoccupied molecular orbital of the dioxirane (* of OOO), which accounts for the electrophilic nature of the dioxirane (52)(53)(54). Both experimental and theoretical studies show that, in general, spiro transition states are favored over planar transition states (52-56, 62, 68, 69, 89, 90, 101-107).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…52-56, 62, 68, 69, 89, 90, and 101-107). The primary frontier orbital interaction for both spiro and planar approaches is between the highest occupied molecular orbital of the alkene ( of CAC) and the lowest unoccupied molecular orbital of the dioxirane (* of OOO), which accounts for the electrophilic nature of the dioxirane (52)(53)(54). Both experimental and theoretical studies show that, in general, spiro transition states are favored over planar transition states (52-56, 62, 68, 69, 89, 90, 101-107).…”
Section: Methodsmentioning
confidence: 99%
“…[52][53][54]. Chiral dioxiranes were shown recently to be effective for asymmetric epoxidation of trans-, trisubstituted , and certain cis-alkenes (92)(93)(94)(95).…”
mentioning
confidence: 99%
“…This reagent is not commercially available due to instability during transport and storage but it can be prepared by reacting acetone and the triple salt Oxone ® (2KHSO 5 ·KHSO 4 ·K 2 SO 4 ) in the laboratory, both on small and large scales (Adam et al, 1987). Adam et al (1989) suggested that pH control between 7.0 and 7.5 by means of phosphate or bicarbonate buffer is essential for in-situ generation of dioxirane as low pH will suppress the critical deprotonation step (from 2 to 3, Scheme 5). In addition, high pH leading to the destruction of dioxirane by oxygen transfer competition from the dioxirane to the substrate or SO 4 2-, and autodecomposition .…”
Section: Dioxiranesmentioning
confidence: 99%
“…Early synthetic applications of these oxidants were restricted to in situ generated dioxiranes. A real milestone for the utilization of dioxiranes in synthetic organic chemistry was the preparation of isolated dimethyldioxirane (DMD) (1) …”
Section: Preparation Of Isolated Dioxiranesmentioning
confidence: 99%